Beta-endorphin Cell Therapy for Cancer Prevention - Zhang, Changqing (Cancer Prev Res (Phila), 2014)
Beta-endorphin (BEP) producing neuron in the hypothalamus plays a key role in brining the stress axis to a state of homeostasis and maintaining body immune defense system. Long-term delivery of BEP to obtain beneficial effect on chemoprevention is challenging, since the peptide rapidly develop tolerance. Using rats as animal model, we show here that transplantation of beta-endorphin neurons into the hypothalamus suppressed carcinogens- and hormone-induced cancers in various tissues and prevented growth and metastasis of established tumors via activation of innate immune functions. Additionally, we show that intracerebroventricular administration of nanosphere-attached dibutyryl cyclic adenosine monophosphate (dbcAMP) increased the number of BEP neurons in the hypothalamus, reduced the stress response, enhanced the innate immune function and prevented tumor cell growth, progression and metastasis. Beta-endorphin neuronal supplementation did not produce any deleterious effects on general health but was beneficial in suppressing age-induced alterations in physical activity, metabolic and immune functions. We conclude that the neuroimmune system has significant control over cancer growth and progression and that activation of the neuroimmune system via beta-endorphin neuronal supplementation/induction may have therapeutic value for cancer prevention and improvement of general health.